Synthesis of Mesoporous Transition‐Metal Phosphates by Polymeric Micelle Assembly. Issue 22 (18th April 2016) - Bastakoti, Bishnu Prasad; Li, Yunqi; Guragain, Sudhina; Pramanik, Malay; Alshehri, Saad M.; Ahamad, Tansir; Liu, Zongwen; Yamauchi, Yusuke
Abstract: Mesoporous iron phosphate (FePO4 ) was synthesized through assembly of polymeric micelles made of asymmetric triblock co‐polymer (polystyrene‐ b ‐poly‐2‐vinylpyridine‐ b ‐ethylene oxide; PS‐PVP‐PEO). The phosphoric acid solution stimulates the formation of micelles with core–shell‐corona architecture. The negatively charged PO4 3− ions dissolved in the solution strongly interact with the positively charged PVP + units through an electrostatic attraction. Also, the presence of PO4 3− ions realizes a bridge between the micelle surface and the metal ions. The removal of polymeric template forms the robust framework of iron phosphate with 30 nm pore diameter and 15 nm wall thickness. Our method is applicable to other mesoporous metal phosphates by changing metal sources. The obtained materials were fully characterized by scanning electron microscope (SEM), transmission electron microscope (TEM), N2 adsorption–desorption, Raman spectroscope, and other techniques. Abstract : Micelle assembly : One‐pot synthesis of mesoporous transition‐metal phosphates with variable metal compositions is reported. This simple and flexible polymeric micelles‐assembly approach allowed an easy synthesis of various mesoporous metal phosphates (see figure).